Action and Structure - Valantiejus, Algimantas (Sociologija. Mintis ir veiksmas, 1997)
The author aims to introduce the reader of the journal with the works of Talcott Parsons by discussing the relation between structure and action. The author suggests that the most important task of sociological analysis of change is the analysis and care for renewal of society’s normative bases. Theoretical mind must consider the origins of thought and action, which always appear in social or sociological context. Reading, translating and interpreting them according to the methodical rules, is equivalent to editing the sociological text and its social implications as well as proposing reasonable paths for action.